Hormonal regulation of lactate production and NHE3 expression by Sertoli cells ex vivo : possible roles for sex steroids hormones in spermatogenesis? - Rato, Luis Pedro Ferreira (2014)
Sertoli cells cells play a key role on the establishment of an adequate luminal environment in the seminiferous tubules of the male reproductive tract. The secretion of the seminiferous tubular fluid (STF), as well as, the control of the pH of this fluid is crucial for male fertility. Sertoli cells express various types of ion membrane transporters that are directly involved on the movement basic and acidic particles across the membrane. Among them, is Na+/H+ exchanger (NHE3), which belongs to the Na+/H+ exchanger family, one of the most relevant epithelial ion transporter families, catalyzes the electroneutral transport of extracellular Na+ for intracellular H+. Several authors have provided confirmation that estrogens and androgens play an important role in male fertility, and regulate fluid transport on the male reproductive tract. On the other hand, as germ cells are unable to use glucose for their energy metabolism (Sertoli cells metabolize glucose and the majority of it is converted to lactate, which is preferentially used by developing germ cells). There is a growing awareness that androgens and estrogens have general metabolic roles that reach far beyond reproductive processes. Thus, is important to understand the role of the sex steroids in expression of NHE3 in Sertoli cells, as wells as, its modulation in metabolism of these “nurse” cells. For this purpose, primary Sertoli cell cultures were prepared from 20 days-old rats in serum-free medium supplemented with insulin, transferrin and selenium supplement (ITS medium) and divided in 7 experimental groups, being subjected to hormonal treatment during 50 hours. The groups were: E2 (17β-estradiol); dihydrotestosterone (DHT); ICI 182,720 (ICI); flutamide (Flut); ICI/ E2; Flut/DHT and control. The hormonal concentration was 100nM for all groups, except control group, which was not treated. The presence of NHE3 in Sertoli cells was confirmed by RT-PCR and western blot analysis. NHE3 was semi-quantified by RT-PCR for all experimental groups, there have been no significant differences when compared to control group. As for, analysis of the metabolites secretion or consumption by Sertoli cell culture, it was recovered 250 μL of the culture medium at 5h,15h, 25, 35h and 50h, after beginning treatment, for hydrogen nuclear magnetic resonance spectra analysis. The results obtained showed that glucose consumption was significantly higher in DHT-treated Sertoli cells after 50 hours than in control conditions or E2-treated cells. Unexpectedly, DHT-treated cells produced less lactate than those treated with E2 or in control conditions. This may be due to several factors such as to a decrease in cellular production of lactate, to a delay in lactate transport to extracellular medium or even to lactate utilization as substrate by DHT-treated cells. In pyruvate consumption there were no significant changes with hormonal treatment, however alanine production was higher in E2-treated cells. In summary, this study demonstrates that sex steroids do not exert significant effects in NHE3 expression by Sertoli cells. It is likely that control of intracellular pH of the Sertoli cells and luminal acidification in seminiferous tubules do not depend on directly of estrogen and androgen actions mediated by its receptors. In other hand, DHT increases glucose consumption in Sertoli cells and E2 increase alanine production. Thus, sex steroids seem to play an important role in modulation of Sertoli cells metabolism.